2021
DOI: 10.2147/nss.s312671
|View full text |Cite
|
Sign up to set email alerts
|

Firefighters Have Cerebral Blood Flow Reductions in the Orbitofrontal and Insular Cortices That are Associated with Poor Sleep Quality

Abstract: Purpose To investigate the cerebral blood flow (CBF) alterations associated with poor sleep quality and memory performance in firefighters. Participants and Methods Thirty-seven firefighters (the FF group) and 37 non-firefighter controls (the control group) with sleep complaints were enrolled in this study. We performed brain arterial spin labeling perfusion magnetic resonance imaging (MRI) and compared the CBF between the two groups using whole-brain voxel-wise analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The OFC also plays an important role in sleep. Park et al (2021) reported that reduced cerebral blood flow in the orbitofrontal and insular cortices was associated with poor sleep quality. We reasoned that one of the mechanisms behind the improvement in sleep may be related to changes in the OFC.…”
Section: Discussionmentioning
confidence: 99%
“…The OFC also plays an important role in sleep. Park et al (2021) reported that reduced cerebral blood flow in the orbitofrontal and insular cortices was associated with poor sleep quality. We reasoned that one of the mechanisms behind the improvement in sleep may be related to changes in the OFC.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 37 firefighters, Park et al. found that reduced cerebral blood flow in the insular cortex was associated with poor sleep quality [ 41 ]. Yin et al.…”
Section: Discussion and Narrative Synthesismentioning
confidence: 99%
“…In terms of cerebral blood flow velocity, an initial increase followed by a decline was observed during sleep [75]. Clinical analyses have showcased the link between suboptimal sleep quality and a decline in cerebral blood flow in areas like the right orbitofrontal and insular cortex [76]. Individuals with NREM disorders manifested reduced CBF in regions such as the parietooccipital lobe (anterior cuneiform lobe), marginal gyrus and cerebellar hemisphere [77].…”
Section: Cerebral Vascular Hemodynamicsmentioning
confidence: 99%